Radiomics of Contrast-Enhanced Computed Tomography: A Potential Biomarker for Pretreatment Prediction of the Response to Bacillus Calmette-Guerin Immunotherapy in Non-Muscle-Invasive Bladder Cancer - Ye, Lei; Chen, Yuntian; Xu, Hui; Wang, Zhaoxiang; Li, Haixia; Qi, Jin; Wang, Jing; Yao, Jin; Liu, Jiaming; Song, Bin (Frontiers in Cell and Developmental Biology, 2022)
Background: Bacillus Calmette-Guerin (BCG) instillation is recommended postoperatively after transurethral resection of bladder cancer (TURBT) in patients with high-risk non-muscle-invasive bladder cancer (NMIBC). An accurate prediction model for the BCG response can help identify patients with NMIBC who may benefit from alternative therapy. Objective: To investigate the value of computed tomography (CT) radiomics features in predicting the response to BCG instillation among patients with primary high-risk NMIBC. Methods: Patients with pathologically confirmed high-risk NMIBC were retrospectively reviewed. Patients who underwent contrast-enhanced CT examination within one to two weeks before TURBT and received ≥ 5 BCG instillation treatments in two independent hospitals were enrolled. Patients with a routine follow-up of at least 1 year at the outpatient department were included in the final cohort. Radiomics features based on CT images were extracted from the tumor and its periphery in the training cohort, and a radiomics signature was built with recursive feature elimination. Selected features further underwent an unsupervised radiomics analysis using the newly introduced method, non-negative matrix factorization (NMF), to compute factor factorization decompositions of the radiomics matrix. Finally, a robust component, which was most associated with BCG failure in one year, was selected. The performance of the selected component was assessed and tested in an external validation cohort. Results: Overall, 132 patients (training cohort, n= 108; external validation cohort, n= 24) were included, including 12 BCG failures in the training and validation cohorts each. NMF revealed five components, of which component 3 was selected for the best discrimination of BCG failure; it had an area under the curve (AUC) of 0.79, sensitivity of 0.79, and specificity of 0.65 in the training set. In the external validation cohort, it achieved an AUC of 0.68, sensitivity of 0.73, and specificity of 0.69. Survival analysis showed that patients with higher component scores had poor recurrence-free survival (RFS) in both cohorts (C-index: training cohort, 0.69; validation cohort, 0.68). Conclusion:The study suggested that radiomics components based on NMF might be a potential biomarker to predict BCG response and RFS after BCG treatment in patients with high-risk NMIBC.